Eine toponymische Reise durch Slowenien aus der Sicht eines deutschsprachigen Reiseführers - Rieger, Mladen (Vestnik za tuje jezike, 2018)
Some 35 years since the publication of the first and, to date, the only systematic piece of work dedicated to translating the Slovenian toponyms into the German language, the use of culture-specific terms in tourist guidebooks on Slovenia need to be analysed anew, the use of toponyms compared with the new findings in the field of translation and inadequate translation solutions pointed out. The findings of the survey have also proved to be efficiently used in educational activities with students of translation studies. Even more so than any other terms, toponyms are associated with places and landscapes, as we use them in an attempt to name the concepts interlacing historical, cultural and social threads that belong to the collective as well as individual memory. Therefore, it would be a mistake to expect that drawing up and editing a dictionary of toponyms, if they appear in translations or foreign language texts, is a task to be completed solely on behalf of the target language and culture. The present contribution aims to analyse the examples of inadequate or less appropriate translation solutions by drawing attention to some particular problems and hint at the possible strategies that may come useful in translating foreign language toponyms.
Keywords: nemščina; prevajanje imen; slovenščina; toponimi; turistični vodniki